Cross-Border Consumption within Kostomuksha and the Kainuu Region - Sheveleva, Anna (Kajaanin ammattikorkeakoulu, 2010)
Usually, national borders are considered to be a barrier to the migration or outward flow of products, services, capital, and people. Nevertheless, differences among countries and cultures can promote cross-border consumption and mobility. This thesis aims to investigate the cross-border consumption phenomena, and to quantify the motivation and regularity of the consumers' purchasing behavior within the Russian town Kostomuksha and the Kainuu region. The survey was conducted by collecting the primary data among the citizens of Kostomuksha, a town in the Russian Republic of Karelia bordering on Finland. The methodology that is used in the research is a quantitative structured self-administered questionnaire with closed questions. The final results were analyzed by using the SPSS program. The findings emphasized that the Russian customers cross the border for shopping and leisure time purposes. The results indicate the importance of the quality and price for the respondents, and demonstrate that cross-border consumption is primarily a rational choice, motivated by the economic reasons such as lower price, better quality, and higher variety of choice. The results of this study, present the general view of the Russian customers. For the deeper understanding the customers' behavior and learning specific target groups it would be reasonable to conduct a futher qualitative research.